2008
DOI: 10.1177/000313480807401205
|View full text |Cite
|
Sign up to set email alerts
|

Fistulogram after Arteriovenous Dialysis Graft Thrombectomy Should be Mandatory

Abstract: The purpose of this study was to determine if fistulogram after prosthetic arteriovenous dialysis graft thrombectomy would reveal underlying lesions, which need correction, and if revision would improve graft patency. One hundred and ninety-two open thrombectomy procedures in 61 patients from January 1, 2000 to July 31, 2005 were reviewed retrospectively. All of the study patients were divided into two groups: In Group I fistulogram was carried out and in Group II no fistulogram was performed. Based on the fis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…We found significant lesions after open thrombectomy that need intervention to correct lesions more than 90% of cases. These data near the result in previous report (78%) from Kuma, et al 11 Regarding one-year primary patency rate, the 26% and 33% rates of one-year primary patency in the endovascular and open thrombectomy groups in our study were near the upper end of the range reported by Tordoir, et al (8-29% and 10-30%), and similar to the rate reported by Hongsakul, et al (28% and 30%).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We found significant lesions after open thrombectomy that need intervention to correct lesions more than 90% of cases. These data near the result in previous report (78%) from Kuma, et al 11 Regarding one-year primary patency rate, the 26% and 33% rates of one-year primary patency in the endovascular and open thrombectomy groups in our study were near the upper end of the range reported by Tordoir, et al (8-29% and 10-30%), and similar to the rate reported by Hongsakul, et al (28% and 30%).…”
Section: Discussionsupporting
confidence: 90%
“…Mostly of patients had total graft thrombosis, only 11 of 25 patients in the endovascular group presented with clinical partial graft thrombosis. Median time from graft thrombosis to treatment was 2 days (range: 1-14) in the endovascular group, and 1 day (range: [1][2][3][4][5][6][7][8][9][10][11][12][13][14] in the open thrombectomy group (p=0.078). A summary of patient and graft data is shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…We and others have previously shown that access thrombosis is almost always the result of outflow stenosis, so monitoring for access failure and in-office correction should minimize missed dialysis sessions and lead to fewer catheters. 4,16 Studies have suggested that balloon-assisted maturation of the fistula may be beneficial. 3 We are still waiting to see more studies to confirm this approach before we start using it.…”
Section: Discussionmentioning
confidence: 99%